Partnering in international agricultural research for development: lessons from the ILAC learning laboratory - CGIAR Institutional Learning and Change Initiative (2010)
This paper presents results of a workshop on partnerships in agricultural research for development (AR4D) organized by the Institutional Learning and Change (ILAC) Initiative of the Consultative Group on International Agricultural Research (CGIAR). The workshop brought together members of the ILAC Learning Laboratory to discuss a wide range of issues related to partnership, including how and why partnership is important for their work, the types of partner they engage with, the various roles played by partners in achieving common objectives, and the types of relationships developed over time. They also discussed obstacles and issues that need attention to enable more effective partnering. Drawing upon these discussions, the workshop participants produced this paper, which summarizes their experiences and draws out common themes and lessons. It presents an overview of the role of partnership in AR4D and summarizes experiences with partnership in the Learning Laboratory, including success factors and areas requiring further attention. Beyond documenting the experiences of the Learning Laboratory members, the paper aims to stimulate dialogue about the use of partnership and improvements needed in the way organizations participate in and manage partnerships in AR4D.